Influencia de la motivación en el pde, en la enseñanza de los estudios sociales, para el rendimiento académico en los alumnos del octavo año de educación básica del colegio nacional Técnico Industrial Dr. Demetrio Aguilera Malta cantón Santa Rosa, año lectivo 2012-2013 - Becerra Rosillo, Dolores Mariana (2013)
The investigative process allowed close up commercial v That motivation positively influences the educational process Social Studies and Academic Achievement of Students Eighth Year of Basic Education National Technical Industrial College Dr. Demetrio Aguilera Malta Santa Rosa Canton, 2012-2013 school year, and That if students are Constantly Improve care motivated classes Increases During His participation in the construction of new knowledge and get better grades that form Do Increased school performance.